2014
DOI: 10.1542/peds.2013-4080
|View full text |Cite
|
Sign up to set email alerts
|

AAP Principles Concerning Retail-Based Clinics

Abstract: The American Academy of Pediatrics views retail-based clinics (RBCs) as an inappropriate source of primary care for pediatric patients, as they fragment medical care and are detrimental to the medical home concept of longitudinal and coordinated care. This statement updates the original 2006 American Academy of Pediatrics statement on RBCs, which flatly opposed these sites as appropriate for pediatric care, discussing the shift in RBC focus and comparing attributes of RBCs with those of the pediatric medical h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 15 publications
0
4
2
Order By: Relevance
“…Our study has potential clinical implications. In the past, some have raised concerns about the quality of care provided in walk-in clinics to the paediatric population 36. Although campaigns on antibiotic stewardship may be needed, our results and existing literature do not support this fear.…”
Section: Discussioncontrasting
confidence: 87%
“…Our study has potential clinical implications. In the past, some have raised concerns about the quality of care provided in walk-in clinics to the paediatric population 36. Although campaigns on antibiotic stewardship may be needed, our results and existing literature do not support this fear.…”
Section: Discussioncontrasting
confidence: 87%
“…Responding to fears of fragmentation of care and potential loss of income, the American Academy of Pediatrics originally opposed and then opened the door to collaboration with these retail-based clinics, citing the benefit to families of improved access. 6 What the innovator's dilemma suggests is that, as these settings of care become increasingly successful, they are likely to leverage their strength to assume a broader share of care delivery, for example, by providing preventive services. The recent merger of CVS, a pharmacy and retail-based provider, and Aetna, a payor, exemplifies this pattern.…”
mentioning
confidence: 99%
“…For those prioritizing convenient and off-hours care, these sites offer advantages in terms of access and potentially expense, especially for low-acuity conditions. Responding to fears of fragmentation of care and potential loss of income, the American Academy of Pediatrics originally opposed and then opened the door to collaboration with these retail-based clinics, citing the benefit to families of improved access . What the innovator’s dilemma suggests is that, as these settings of care become increasingly successful, they are likely to leverage their strength to assume a broader share of care delivery, for example, by providing preventive services.…”
mentioning
confidence: 99%
“…6–8 In one study, 37% of pediatric providers reported suboptimal care for their patients seen in adult outpatient retail clinics. 9…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] In one study, 37% of pediatric providers reported suboptimal care for their patients seen in adult outpatient retail clinics. 9 Pediatric Quality and Safety Due to the number of unnecessary antibiotics prescribed in the outpatient setting and the AAP's concern regarding pediatric patients seeking care in retail clinics, we decided to develop a QI project focused on the accurate diagnosis and treatment of AOM in our hospital-owned pediatric retail clinic. The specific aim for this improvement project was to increase the percentage of compliant AOM diagnostic and treatment bundles from 42% to 95% for pediatric patients seen in an outpatient pediatric hospital-owned retail clinic by July 1, 2020.…”
Section: Introductionmentioning
confidence: 99%